2021
DOI: 10.1007/s10517-021-05358-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Administration of NOD-2 (MDP) and TLP-4 (LPS) Ligands to Bone Marrow Donors 24 h before Transplantation Increases the Content of Multipotent Stromal Cells (MSCs) in Bone Marrow Grafts in CBA Mice Compared to the Total Result of Their Isolated Administration

Abstract: In 3-month bone marrow transplants of CBA mice from bone marrow donors receiving single injections of TLR-4 ligand (LPS) or NOD-2 ligand (muramyl dipeptide, MDP) 24 h before transplantation, an increase in the total number of MSCs (by 2.6 and 1.9 times, respectively), as well as a slight increase in the number of nuclear cells and the mass of bone capsules (by 1.3 and 1.2 times) were observed. After combined administration of MDР and LPS to donors, the total content of MSCs in the grafts was higher by 1.6 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Interesting data on a 1.9-fold increase in the number of multipotent bone marrow stem cells were obtained in bone marrow transplants of mice from bone marrow donors who received single injections of MDP 24 h before transplantation [121]. These results confirm previously obtained data on the correction of cytopenia during chemotherapy [119].…”
Section: Muramyl Peptide Regulation Of Intracellular Signaling Pathwayssupporting
confidence: 84%
“…Interesting data on a 1.9-fold increase in the number of multipotent bone marrow stem cells were obtained in bone marrow transplants of mice from bone marrow donors who received single injections of MDP 24 h before transplantation [121]. These results confirm previously obtained data on the correction of cytopenia during chemotherapy [119].…”
Section: Muramyl Peptide Regulation Of Intracellular Signaling Pathwayssupporting
confidence: 84%
“…Therefore, LPS is commonly used in scientific research to induce liver injury in the ALF models. Animal model studies have shown that LPS‐induced liver injury is associated with increased reactive oxygen species (ROS) production, inflammatory factor secretion, and hepatocyte apoptosis 9,11 . Human fetal hepatocyte line, L02, has the advantage of excellent proliferative capacity and exhibits good liver function in vitro and in an ALF model 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Animal model studies have shown that LPS‐induced liver injury is associated with increased reactive oxygen species (ROS) production, inflammatory factor secretion, and hepatocyte apoptosis. 9 , 11 Human fetal hepatocyte line, L02, has the advantage of excellent proliferative capacity and exhibits good liver function in vitro and in an ALF model. 12 Moreover, LPS induced L02 cell inflammatory injury has been widely used to study ALF in vitro.…”
Section: Introductionmentioning
confidence: 99%